Answer:
x=-3
Step-by-step explanation:
Place like terms on the same side.
Keep in mind when a term is moved from its original position, it changes sign.
x+x=-3-3
2x=-6
x=-3
Answer:
B
Step-by-step explanation:
The answer to (-4.5)(-6)(5.4)= 137.7
Answer:
see below
Step-by-step explanation:
The exponent rules that apply are ...
(a^b)(a^c) = a^(b+c)
a^-b = (1/a)^b
(a^b)^c = a^(b·c)
_____
These let you rewrite the given function as ...
f(x) = (3^(2x))(3^1) = 3(3^(2x)) = 3(3^2)^x = 3·9^x
and
f(x) = 3^(2x+1) = (3^-1)^(-(2x+1)) = (1/3)^-(2x+1)
Answer:
8.06
Step-by-step explanation:
a^2 + b^2 = c^2
4^2 + 7^2 = c^2
16 + 49 = c^2
65= c^2
Find the square root of 65
8.06